Efgartigimod as a promising add-on therapy for myasthenic crisis: a prospective case series - Song, Jie; Wang, Haiyan; Huan, Xiao; Jiang, Qilong; Wu, Zongtai; Yan, Chong; Xi, Jianying; Zhao, Chongbo; Feng, Huiyu; Luo, Sushan (Frontiers in Immunology, 2024)
Efgartigimod is effective and well-tolerated in patients with anti-acetylcholine receptor (AChR) antibody-positive generalized myasthenia gravis (MG). However, the therapeutic potential and the safety profile of efgartigimod in myasthenic crisis (MC) remained largely unknown. This is an observational, prospective, multicenter, real-world study to follow 2 MC patients who initiated efgartigimod as a first-line rescue therapy and 8 cases who used it as an add-on therapy. Baseline demographic features and immunotherapies were collected, and the MG-activities of daily living (MG-ADL) scale was evaluated every week since efgartigimod treatment for 8 weeks. Additionally, serum IgG and anti-AChR antibody levels and the peripheral CD4+ T lymphocytes were measured before and after one cycle of treatment. Ten patients with MC were enrolled in the study, including 9 anti-AChR antibody positive and 1 anti-muscle-specific kinase (MuSK) positive. All patients were successfully weaned from the ventilation after receiving efgartigimod treatment, with a length of 10.44±4.30 days. After one cycle of infusions, the MG-ADL score reduced from 15.6±4.4 at the baseline to 3.4±2.2, while the corticosteroid dose was tapered from 55.0±20.7 mg to 26.0±14.1 mg. The proportions of regulatory T cells and naïve T cells (% in CD4+ T) significantly decreased post-efgartigimod treatment (5.48±1.23 vs. 6.90±1.80, P=0.0313, and 34.98±6.47 vs. 43.68±6.54, P=0.0313, respectively). hese findings validated the rapid action of efgartigimod in facilitating the weaning process with a good safety profile in patients with MC.